Silver Rasbora Bekasam Using Various Processed Rice on Microbiological and Organoleptic Properties - Priyanto, Anugerah Dany (Program Studi Teknologi Pangan, 2018)
Silver rasbora fish is a fresh fish that is often found in the traditional market, but the product has decreased in quality during its distribution chain. Bekasam is a spontaneous fermented fish product by adding salt as microorganism selective material and rice as source of carbohydrates for expected microorganisms. Aims of this study were to innovate silver rasbora fish processing into bekasam and explore various kinds of processed rice as fermentation media. This study was used by a completely randomized design (CRD) with factor was processed rice, particulary uncooked rice, cooked rice, karak, and nasi aking that given to fish by 50% (w/w). Observations were made on fresh silver rasbora fish and bekasam to compare the quality of fermented products. The observed parameters included total lactic acid bacteria and organoleptic. The results showed that processed rice had significantly effect on total LAB toward bekasam (P 0.05). Total LAB of bekasam which were fermented by various kinds of processed rice which can classified as probiotic food between 8.12-8.75 log CFU / g. Likewise on the organoleptic properties had significant effect (P 0.05). The best product was obtained from the bekasam using karak as fermentation media. The bekasam had total LAB of 8.12 log CFU / g and also had organoleptic properties with a high level of preference compared to the others. Hopefully, this research can increases the added value of silver rasbora fish and better quality than fresh products.